Pembentukan Karakter Politik Anak Usia Dini Dalam Merespons Kampanye Politik 2024 - Azid, Yusuf Teja; Listyani, Refti Handini (Paradigma, 2024)
The family has an important role in the process of socialization and education development of a child. Political education is important today, because efforts to build and develop political awareness. The involvement of mothers’ roles in socializing early childhood in the 2024 political campaign in Labuhan Village, Brondong District, Lamongan Regency. is something that needs to be considered. The purpose of this study is to Identifying the Objective Conditions of the Role of Mothers in the Formation of Early Childhood Political Character in Responding to the 2024 Campaign in Labuhan Village Analyzing the Role of Mothers in the Socialization Process, Analyzing the Influence of Political Values in Socialization. Identifying Environmental Influences and Family Social Status. The research method used in this study is a qualitative research method, theory from George Herbert Mead and supported by Max Weber theory. The results of this study show that there is a significant role of mothers in children’s political socialization, mothers have a very important role in shaping the understanding and political attitudes of early childhood. Through daily interactions, political discussions, and participation in political activities, mothers play a key role in shaping the political consciousness of the younger generation. There are variations in children’s responses to politics that are influenced by the mother’s level of involvement, the family’s economic environment, and other factors. Role of Community Leaders: In addition to mothers, community leaders also have a significant influence in shaping political understanding in Labuan Village.